Preparation method of photocatalytic material with amorphous defects on surface

The electro-enhanced transient high-energy gas-phase plasma technology forms an amorphous defect structure with oxygen vacancies on the photocatalytic materials, which solves the problems of limited photoresponse range and low carrier separation efficiency of photocatalytic materials, and significantly improves the catalytic activity of the material.

CN119869625APending Publication Date: 2025-04-25CHANGSHA INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510066160.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The photoresponse range of existing photocatalytic materials is limited, and the photogenerated carrier separation efficiency is low, resulting in a reduced catalytic activity.

Method used

Electrically enhanced transient high-energy gas-phase plasma technology is used to generate transient high-temperature gas-phase plasma in the photocatalytic material area through high-frequency square wave pulse voltage, achieving rapid reduction processing and forming an amorphous defect structure doped with oxygen vacancy.

Benefits of technology

It effectively broadens the photoresponse range of photocatalytic materials, improves carrier migration efficiency, enhances the catalytic activity of the materials, and avoids side reactions such as the generation of deep oxygen vacancies and crystal phase transitions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869625A_ABST
    Figure CN119869625A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a photocatalytic material with amorphous defects on the surface, which comprises the following steps of: applying high-frequency direct-current square-wave pulse voltage to the photocatalytic material between a positive electrode plate and a negative electrode plate, gathering a large number of high-energy electrons in a photocatalytic material area, and generating electrically enhanced transient high-energy gas-phase plasma; rapid reduction treatment on the photocatalytic material is realized, so that an oxygen vacancy doped amorphous defect structure is generated on the crystal surface of the photocatalytic material, and finally the photocatalytic material with amorphous defects on the surface is prepared. According to the preparation method disclosed by the invention, the generation and migration rate of photon-generated carriers is promoted, and the activity and stability of the photocatalytic material are effectively improved. In addition, the process is simple, efficient, free of complex equipment and process conditions, low in production energy consumption and suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and more specifically, to a method for preparing a photocatalytic material with surface amorphous defects. Background Art

[0002] There are two major challenges in improving the activity of photocatalytic materials: first, the light response range is limited. For example, titanium dioxide only absorbs ultraviolet light (<365nm) due to its wide energy gap, resulting in a low yield of photogenerated electron-hole pairs; second, the separation efficiency of photogenerated carriers is low, a large number of carriers recombine in the lattice, and only a few can reach the surface to participate in the reaction. To solve the above problems, thermal reduction treatment, chemical reduction treatment, and electrochemical reduction are usually used to synthesize reductive photocatalytic materials to broaden their light response range and accelerate the migration of photogenerated carriers.

[0003] Surface amorphous defects, also known as surface amorphization, have advantages such as excellent electronic conductivity, excellent visible light absorption, large specific surface area, abundant surface active sites, and tunable band structure. At present, the gas phase plasma reducing atmosphere (hydrogen, argon, ammonia, etc.) heat treatment technology is widely used to obtain metal oxide surface amorphous defects, which are typically characterized by the generation of surface lattice disordered structure and oxygen vacancy defects. The gas phase plasma reducing atmosphere heat treatment technology has the following defects: (1) It is easy to produce deep and high-concentration oxygen vacancy defects. Because the charged particles of the gas phase plasma have a long mean free path, high-energy collisions will occur on the crystal surface and generate a large number of deep oxygen vacancy defects, forming electron capture traps and causing the recombination and consumption of electron-hole pairs, resulting in a decrease in the catalytic activity of the material. (2) The gas phase plasma is accompanied by a high-temperature annealing reaction, which will induce side reactions such as crystal phase transition. (3) The gas phase plasma annealing rate is slow, which will destroy the stability of the surface amorphous defects. (4) The concentration of the gas-phase plasma reducing atmosphere is low (e.g., the hydrogen content is about 1%–2%), which limits the surface modification rate. Summary of the invention

[0004] Based on the above technical problems existing in the prior art, the present invention provides a method for preparing photocatalytic materials with surface amorphous defects by using electrically enhanced transient high-energy gas-phase plasma technology, which creates an extreme surface modification environment of ultra-high temperature reduction and rapid annealing by increasing the single pulse energy of plasma and compressing the rising / falling edge pressure of plasma voltage. This method has the characteristics of efficient reduction, low thermal effect, and mild surface modification. By adjusting the control parameters, the amorphous defect structure doped with surface oxygen vacancies can be efficiently and accurately constructed, effectively inhibiting the generation of deep oxygen vacancies, and effectively improving the activity of photocatalytic materials.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing a photocatalytic material with surface amorphous defects, wherein a high-frequency square wave pulse DC voltage is applied to the photocatalytic material between positive and negative electrodes, a large number of high-energy electrons are gathered in the photocatalytic material region and electrically enhanced transient high-energy gas-phase plasma is generated, thereby achieving rapid reduction treatment of the photocatalytic material, generating an oxygen vacancy-doped amorphous defect structure on the crystal surface of the photocatalytic material, and finally preparing a photocatalytic material with surface amorphous defects.

[0007] In some embodiments, the method comprises the following steps:

[0008] S1. Preparing a precursor mixed slurry: fully mixing a photocatalytic material, a reducing agent and water in a certain proportion to obtain a precursor;

[0009] S2. Fill the precursor between the non-metallic electrode plates, then apply a high-frequency DC square wave pulse voltage to the non-metallic electrode plates to generate transient high-temperature gas-phase plasma in the photocatalytic material area, and perform rapid in-situ reduction treatment on the photocatalytic material to obtain the photocatalytic material with surface amorphous defects.

[0010] The photocatalytic material is mixed with a reducing agent and water to prepare a precursor, which is then placed between non-metallic electrode plates and a high-frequency DC square wave pulse voltage is applied. The reducing agent undergoes a high-temperature reduction reaction with the photocatalytic material under a high-temperature environment, and water can be cracked by transient high-temperature plasma to generate hydrogen, promoting high-temperature reduction. The synergistic effect of the two can enhance the reduction effect on the photocatalytic material.

[0011] In some embodiments, the voltage frequency is 1–5 kHz, the duty cycle is 50–100%, the voltage is 200–1500 V, the instantaneous current is controlled at 10–20 A, and the average current is controlled at 5–10 A; the applied pulse energy is 0.1–5 joules; the voltage application time is greater than 0.01 seconds, and the voltage rise / fall edge is 10–200 microseconds.

[0012] In some embodiments, the non-metallic electrode plate includes at least one of a graphite electrode plate, a graphene electrode plate, an activated carbon electrode plate, and a biochar electrode plate.

[0013] In some embodiments, the mass ratio of the photocatalytic material, the reducing agent and water is 100:0.01-10:0-4.

[0014] In some embodiments, the reducing agent includes at least one of graphene, graphyne, Lewis acid, oxalic acid, iron powder, and copper powder.

[0015] In some embodiments, the photocatalytic material includes at least one of titanium dioxide, zinc oxide, tungsten trioxide, tin dioxide, ferric oxide, cuprous oxide, graphite carbon nitride, cadmium sulfide, zinc sulfide, molybdenum disulfide, bismuth vanadate, bismuth tungstate, bismuth molybdate, metal organic framework materials, covalent organic framework materials, and two-dimensional material MXene.

[0016] In some embodiments, the method comprises the following steps:

[0017] S1. Preparing a precursor mixed slurry: fully mixing a photocatalytic material, a reducing agent and water to obtain a precursor mixed slurry;

[0018] S2. Assembly of the discharge device: The discharge device comprises an electrolytic cell, electrodes and non-metallic electrode plates; two electrodes are arranged oppositely on two sides of the electrolytic cell, and a plurality of non-metallic electrode plates are arranged in parallel and spaced apart in the electrolytic cell and connected to the two electrodes at both ends; the electrodes are porous metal foams; and the electrolytic cell is a high temperature resistant insulating container;

[0019] S3. The precursor mixed slurry prepared in step S1 is uniformly filled into the cavity formed between the non-metallic electrode plates, and then a high-frequency square wave voltage is applied to the two electrodes to generate a transient high-temperature gas-phase plasma in the cavity area, so that the photocatalytic material undergoes a high-temperature reduction reaction to obtain a photocatalytic material with surface amorphous defects.

[0020] In some embodiments, the electrolytic cell is made of at least one of silicon oxide, silicon nitride, zirconium oxide, and mullite.

[0021] The present invention also provides a photocatalytic material with surface amorphous defects obtained by the preparation method of any of the above embodiments, wherein the photocatalytic material has an amorphous defect structure on its crystal surface and produces oxygen vacancy defects with a content of 0.1%-10% at a thickness of 0.1-5 nanometers from the amorphous defect surface.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] The present invention applies a high-frequency DC square wave pulse voltage to the photocatalytic material between the positive and negative electrode plates, so that a large number of high-energy electrons gather in the photocatalytic material area, thereby generating a transient high-temperature gas-phase plasma in the photocatalytic material area, and the reducing agent reacts with the photocatalytic material under high temperature conditions to achieve rapid reduction of the photocatalytic material, resulting in an oxygen vacancy-doped amorphous defect structure (such as Figure 1At the same time, the generated transient high-temperature gas-phase plasma has high pressure (2-3Mpa) and strong shock wave characteristics, forming a local high-temperature and high-pressure gas-phase plasma barrier in the photocatalytic material area, isolating oxygen in the air from entering the high-temperature gas-phase plasma area, thereby avoiding the side reaction of high-temperature oxidation to eliminate oxygen vacancies.

[0024] Compared with the existing gas-phase plasma modification methods, the electrically enhanced transient high-energy gas-phase plasma technology proposed in the present invention creates an extreme surface modification environment of ultra-high temperature reduction and rapid annealing by increasing the single-pulse energy of plasma and compressing the rising / falling edge pressure of plasma voltage. This technology has the characteristics of high-efficiency reduction, low thermal effect, and mild surface modification. The beneficial effects of this method include: (1) effectively avoiding deep and high-concentration oxygen vacancy defects and ensuring the efficiency of carrier migration; (2) avoiding side reactions such as crystal phase change caused by the high-temperature annealing reaction of the existing gas-phase plasma and ensuring the stability of the crystal phase; (3) avoiding the destruction of the surface amorphous defect structure caused by the slow annealing rate of the existing gas-phase plasma and ensuring the stability of the surface amorphous defects; (4) Compared with the existing technology, the electrically enhanced transient high-energy gas-phase plasma technology significantly improves the surface modification rate and realizes the surface modification of photocatalytic materials in batches at the second level.

[0025] In addition, the surface amorphous defect structure formed by the method of the present invention can protect the oxygen vacancy defects in the subsurface layer from the oxidation effect of air, so that the treated photocatalytic material has excellent environmental stability.

[0026] The method for preparing a surface amorphous defect photocatalytic material of the present invention improves the visible light absorption of the photocatalytic material, promotes the generation and migration rate of photogenerated carriers, and effectively improves the activity of the photocatalytic material; and by adjusting the energy and action time of the transient high-temperature gas-phase plasma, the thickness of the amorphous defects (0.1-10nm) and the concentration of the oxygen vacancy defects (0.1%-10%) can be precisely controlled, thereby achieving precise control of the energy band structure of the photocatalytic material.

[0027] The process involved in the present invention is simple and efficient, does not require complicated equipment and process conditions, has low production energy consumption, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the preparation of surface amorphous defect photocatalytic materials for this application;

[0029] Figure 2 A schematic diagram of a discharge device for preparing a surface amorphous defect photocatalytic material according to an embodiment of the present invention;

[0030] Among them, 1-electrode clamp positive electrode, 2-foam metal electrode, 3-non-metallic electrode plate, 4-electrolyzer, 5-precursor, 6-electrode clamp negative electrode. DETAILED DESCRIPTION

[0031] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0033] The raw materials and equipment used in the following examples are as follows:

[0034] raw material:

[0035] Photocatalytic material: titanium dioxide powder;

[0036] Reducing agent: graphene;

[0037] Solvent: water;

[0038] Experimental equipment:

[0039] Ball mill: used to mix and disperse the precursor mixed slurry;

[0040] Discharge device: Figure 2 As shown, it includes an electrolytic cell 4, a foam copper electrode 2, an activated carbon electrode plate 3, an electrode clamp positive electrode 1 and an electrode clamp negative electrode 6; two foam copper electrodes 2 are arranged oppositely on both sides of the electrolytic cell 4, and a plurality of activated carbon electrode plates 3 are arranged at intervals in the electrolytic cell 4 and connected to the two foam copper electrodes 2 at both ends; the electrolytic cell 4 is a high temperature resistant insulating zirconia electrolytic cell;

[0041] Discharge power supply: square wave pulse power supply, parameter settings are 3kHz, 600V, duty cycle 50%, voltage rising and falling edges are 50-100 microseconds, single pulse energy is 2-4 joules.

[0042] Example 1 Preparation of surface amorphous defect titanium oxide under different ratios of photocatalytic material and reducing agent

[0043] Prepare the precursor mixed slurry: add anatase titanium dioxide powder, graphene and deionized water (H2O) into a ball mill according to a certain mass ratio (see Table 1); start the ball mill to mix and disperse until a uniform precursor mixed slurry is formed, adjust the speed of the ball mill to 400r / min, and the ball milling time to 30min;

[0044] like Figure 2, filling the precursor 5 into the discharge cavity formed by the zirconium oxide electrolytic cell 4 and the activated carbon electrode plate 3;

[0045] Apply a high-frequency square wave voltage with parameters set to 3kHz, 600V, a duty cycle of 50%, a voltage rise and fall of 50–100 microseconds, and a single pulse energy of 2–4 joules. Connect the square wave pulse power supply to both ends of the electrode (such as Figure 2 , the positive and negative electrodes are connected to the positive electrode 1 and the negative electrode 6 of the electrode clamp respectively), the power is turned on, a large number of high-energy electrons gather in the precursor area, and a transient high-temperature gas-phase plasma is generated. Water is cracked by the transient high-temperature plasma to generate hydrogen, which reacts with titanium dioxide to undergo a high-temperature reduction reaction, thereby achieving a rapid reduction treatment of titanium dioxide. The discharge is continued for 5 seconds, so that titanium dioxide undergoes a reduction reaction under the action of graphene;

[0046] After the discharge is completed and the power is turned off, the electrolytic cell is carefully opened and the reduced titanium dioxide photocatalytic material is taken out. After natural cooling, titanium dioxide with amorphous defects on the surface (TiO x , 1.6≤x<2) photocatalytic powder material.

[0047] Table 1 Mass ratio of anatase titanium dioxide powder, graphene and deionized water

[0048]

[0049] The synthesized titanium oxide photocatalytic powder material with surface amorphous defects was subjected to UV-visible diffuse reflectance spectroscopy and visible light degradation dye test. The UV-visible diffuse reflectance spectroscopy is used to test the visible light absorption characteristics of the prepared titanium oxide photocatalytic powder material with surface amorphous defects; the visible light degradation dye test is used to characterize the photocatalytic activity of the prepared titanium oxide photocatalytic powder material with surface amorphous defects. The specific test methods are as follows:

[0050] Visible light degradation dye test experiment, parameters: visible light (420–800nm), light power density: 700mW / cm 2 , dye: Rhodamine B (1 mg / L, 50 ml), photocatalyst dosage 50 mg.

[0051] The specific experimental content is: Pour 50ml of 1mg / L Rhodamine B solution and 50mg of the prepared photocatalyst into a beaker, place it on a magnetic stirrer, start stirring, and ensure that the dye solution and the photocatalyst are evenly mixed. Place a visible light source above the quartz beaker and adjust the position of the light source to ensure that the light emitted by the light source can be evenly irradiated on the dye solution. Adjust the power density of the light source to 700mW / cm 2, measured and calibrated using an optical power meter. Turn on the light source and start the photocatalytic degradation experiment. Use a pipette to take out 1 ml of the reaction solution from the quartz beaker every 10 minutes, put it into a UV-visible spectrophotometer, and measure its absorbance at the maximum absorption wavelength of Rhodamine B. The experimental process lasts for 60 minutes. Calculate the degradation rate based on the initial concentration and the concentration at each time point.

[0052] Degradation rate = (initial concentration - current concentration) / initial concentration × 100%.

[0053] Sample 1, sample 2, sample 3, and sample 4 were tested for visible light degradation of dyes.

[0054] The test results are shown in Table 2 and Table 3:

[0055] Table 2 UV-visible diffuse reflectance spectrum results

[0056] sample Sample 1 Sample 2 Sample 3 Sample 4 Absorption edge(eV) 3.1 3.0 2.8 2.9

[0057] Table 3 Test results of visible light degradation dyes

[0058] sample Sample 1 Sample 2 Sample 3 Sample 4 Degradation rate 75% 82% 98% 95%

[0059] Example 2 Preparation of titanium oxide with surface amorphous defects under different water contents

[0060] The preparation method and equipment used in this embodiment are the same as those in Example 1, except that the moisture content of the precursor mixed slurry is different. The mass ratios of the raw materials are shown in Table 4.

[0061] Table 4 Proportion formula of anatase titanium dioxide powder, graphene and deionized water

[0062]

[0063] The titanium oxide photocatalytic powder with amorphous defects on the surface obtained in this example was subjected to ultraviolet-visible diffuse reflectance spectroscopy and visible light degradation dye tests. The specific test methods are as follows:

[0064] Visible light degradation dye test experiment, parameters: visible light (420–800nm), light power density: 700mW / cm 2 , dye: Rhodamine B (2 mg / L, 50 ml), photocatalyst dosage 50 mg.

[0065] The specific experimental content is: Pour 50ml of 1mg / L Rhodamine B solution and 50mg of the prepared photocatalyst into a beaker, place it on a magnetic stirrer, start stirring, and ensure that the dye solution and the photocatalyst are evenly mixed. Place a visible light source above the quartz beaker and adjust the position of the light source to ensure that the light emitted by the light source can be evenly irradiated on the dye solution. Adjust the power density of the light source to 700mW / cm 2 , measured and calibrated using an optical power meter. Turn on the light source and start the photocatalytic degradation experiment. Use a pipette to take out 1 ml of the reaction solution from the quartz beaker every 10 minutes, put it into a UV-visible spectrophotometer, and measure its absorbance at the maximum absorption wavelength of Rhodamine B. The experimental process lasts for 60 minutes. Calculate the degradation rate based on the initial concentration and the concentration at each time point.

[0066] Degradation rate = (initial concentration - current concentration) / initial concentration × 100%.

[0067] Sample 5, Sample 6, Sample 7, and Sample 8 were tested for visible light degradation of dyes.

[0068] The test results are shown in Table 5 and Table 6:

[0069] Table 5 UV-visible diffuse reflectance spectrum results

[0070] sample Sample 5 Sample 6 Sample 7 Sample 8 Absorption edge(eV) 2.8 2.72 2.55 2.56

[0071] Table 6 Test results of visible light degradation dyes

[0072] sample Sample 5 Sample 6 Sample 7 Sample 8 Degradation rate 80% 85% 93% 92%

[0073] Note: The concentration of Rhodamine B solution was set to 2 mg / L.

[0074] Example 3 Preparation of titanium oxide with surface amorphous defects under different discharge time conditions

[0075] The preparation method and equipment used in this embodiment are the same as those in Example 1. The mass ratio of the raw materials used is 100:4:1. The difference is that the discharge time is different. The mass ratios of the raw materials are shown in Table 7.

[0076] Table 7 Different discharge time conditions

[0077] sample Sample 9 Sample 10 Sample 11 Sample 12 Discharge time / s 5 10 15 20

[0078] The titanium oxide photocatalytic powder with amorphous defects on the surface obtained in this example was subjected to ultraviolet-visible diffuse reflectance spectroscopy and visible light degradation dye tests. The specific test methods are as follows:

[0079] Visible light degradation dye test experiment, parameters: visible light (420–800nm), light power density: 700mW / cm 2 , dye: Rhodamine B (2 mg / L, 50 ml), photocatalyst dosage 50 mg.

[0080] The specific experimental content is: Pour 50ml of 1mg / L Rhodamine B solution and 50mg of the prepared photocatalyst into a beaker, place it on a magnetic stirrer, start stirring, and ensure that the dye solution and the photocatalyst are evenly mixed. Place a visible light source above the quartz beaker and adjust the position of the light source to ensure that the light emitted by the light source can be evenly irradiated on the dye solution. Adjust the power density of the light source to 700mW / cm 2 , measured and calibrated using an optical power meter. Turn on the light source and start the photocatalytic degradation experiment. Use a pipette to take out 1 ml of the reaction solution from the quartz beaker every 10 minutes, put it into a UV-visible spectrophotometer, and measure its absorbance at the maximum absorption wavelength of Rhodamine B. The experimental process lasts for 30 minutes. Calculate the degradation rate based on the initial concentration and the concentration at each time point.

[0081] Degradation rate = (initial concentration - current concentration) / initial concentration × 100%.

[0082] Sample 9, sample 10, sample 11, and sample 12 were tested for visible light degradation dyes.

[0083] The test results are shown in Table 8 and Table 9:

[0084] Table 8 UV-visible diffuse reflectance spectrum results

[0085] sample Sample 1 Sample 2 Sample 3 Sample 4 Absorption edge(eV) 2.55 2.34 2.37 2.41

[0086] Table 9 Test results of visible light degradation dyes

[0087] sample Sample 1 Sample 2 Sample 3 Sample 4 Degradation rate 76% 93% 91% 90%

[0088] Note: The concentration of Rhodamine B solution was set to 2 mg / L, and the dye degradation process was 30 min.

[0089] In summary, in the process of preparing photocatalytic materials with surface amorphous defects, the ratio of photocatalytic materials, reducing agents, deionized water, and flash plasma discharge time will have an important impact on the light absorption characteristics and photocatalytic performance of the synthesized materials. Therefore, the synthesis parameters need to be strictly controlled in the actual experimental production process.

[0090] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a photocatalytic material with surface amorphous defects, characterized in that: By applying a high-frequency square wave pulse DC voltage to the photocatalytic material between the positive and negative electrodes, a large number of high-energy electrons are gathered in the photocatalytic material area and electrically enhanced transient high-energy gas-phase plasma is generated, thereby achieving rapid reduction treatment of the photocatalytic material, causing an oxygen vacancy-doped amorphous defect structure to be generated on the crystal surface of the photocatalytic material, and ultimately obtaining a photocatalytic material with surface amorphous defects.

2. The method for preparing a photocatalytic material with surface amorphous defects according to claim 1, characterized in that: The following steps are involved: S1. Preparing a precursor mixed slurry: fully mixing a photocatalytic material, a reducing agent and water in a certain proportion to obtain a precursor; S2. Fill the precursor between the non-metallic electrode plates, and then apply a high-frequency DC square wave pulse voltage to the non-metallic electrode plates to gather a large number of high-energy electrons in the photocatalytic material area and generate electrically enhanced transient high-energy gas-phase plasma, and perform rapid in-situ reduction treatment on the photocatalytic material to obtain the photocatalytic material with surface amorphous defects.

3. The method for preparing a photocatalytic material with surface amorphous defects according to claim 2, characterized in that: The voltage frequency is 1–5kHz, the duty cycle is 50–100%, the voltage is 200–1500V, the instantaneous current is controlled at 10–20A, and the average current is controlled at 5–10A; The applied pulse energy is 0.1–5 joules; the applied voltage time is greater than 0.01 second, and the voltage rise / fall edge is 10–200 microseconds.

4. The method for preparing a photocatalytic material with surface amorphous defects according to claim 2, characterized in that: The non-metallic electrode plate includes at least one of a graphite electrode plate, a graphene electrode plate, an activated carbon electrode plate, and a biochar electrode plate.

5. The method for preparing a photocatalytic material with surface amorphous defects according to claim 2, characterized in that: The mass ratio of the photocatalytic material, the reducing agent and water is 100:0.01-10:0-4.

6. The method for preparing a photocatalytic material with surface amorphous defect engineering according to claim 2, characterized in that: The reducing agent includes at least one of graphene, graphyne, Lewis acid, oxalic acid, iron powder and copper powder.

7. The method for preparing a photocatalytic material with surface amorphous defects according to claim 2, characterized in that: The photocatalytic material includes at least one of titanium dioxide, zinc oxide, tungsten trioxide, tin dioxide, ferric oxide, cuprous oxide, graphite carbon nitride, cadmium sulfide, zinc sulfide, molybdenum disulfide, bismuth vanadate, bismuth tungstate, bismuth molybdate, metal organic framework materials, covalent organic framework materials, and two-dimensional material MXene.

8. The method for preparing a photocatalytic material with surface amorphous defects according to any one of claims 2 to 7, characterized in that: The following steps are involved: S1. Preparing a precursor mixed slurry: fully mixing a photocatalytic material, a reducing agent and water to obtain a precursor mixed slurry; S2. Discharge device assembly: the discharge device comprises an electrolytic cell, electrodes and non-metallic electrode plates; Two electrodes are arranged oppositely on both sides of the electrolytic cell, and a plurality of non-metallic electrode plates are arranged in parallel and spaced apart in the electrolytic cell and connected to the two electrodes at both ends; the electrodes are porous metal foams; and the electrolytic cell is a high temperature resistant insulating container; S3. The precursor mixed slurry prepared in step S1 is uniformly filled into the cavity formed between the non-metallic electrode plates, and then a high-frequency square wave voltage is applied to the two electrodes to generate a transient high-temperature gas-phase plasma in the cavity area, so that the photocatalytic material undergoes a high-temperature reduction reaction to obtain a photocatalytic material with surface amorphous defects.

9. The method for preparing a photocatalytic material with surface amorphous defects according to claim 8, characterized in that: The material of the electrolytic cell is at least one of silicon oxide, silicon nitride, zirconium oxide and mullite.

10. The photocatalytic material having amorphous surface defects obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The photocatalytic material crystal surface layer generates an amorphous defect structure, and generates oxygen vacancy defects with a content of 0.1%-10% at a thickness of 0.1-5 nanometers away from the amorphous defect surface.